Non-Performing Loan and Profitability of Private Commercial Banks in Nepal - Gnawali , Bindu (Patan Prospective Journal, 2025)
This study aims to examine the effect of non-performing loans (NPL) on the profitability of commercial banks in Nepal. In the context of the rapidly evolving banking sector, where institutions face challenges related to loans, financial performance plays a crucial role. The research focuses on 20 commercial banks, selecting a sample of 10 banks through judgmental sampling, covering the period from 2013/14 to 2022/23. Data for the study were obtained from the annual reports of the chosen banks. A causal-comparative research design was used to analyze and interpret the data, which was processed using Microsoft Excel and SPSS version 25. The study found a significant negative relationship between Cash Reserve Ratio and Bank Size with Return on Assets and Return on Equity, while the other independent variables had no significant impact. Furthermore, CRR and BS were negatively correlated, while NPL and Capital Adequacy Ratio (CAR) positively and significantly affected both ROA and ROE. The Credit Deposit Ratio (CDR) did not have a significant influence on the returns, highlighting its lesser importance compared to other financial factors. The findings suggest that banks with higher capital reserves and greater risk exposure (through NPLs) tend to perform better financially, while larger banks and those with higher cash reserves may face difficulties in maintaining strong profitability.